Lacticaseibacillus rhamnosus R0011 secretome attenuates Salmonella enterica serovar Typhimurium secretome-induced intestinal epithelial cell monolayer damage and pro-inflammatory mediator production in intestinal epithelial cell and antigen-presenting cell co-cultures - Jeffrey, Michael P.; MacPherson, Chad W.; Tompkins, Thomas A.; Green-Johnson, Julia M. (Frontiers in Microbiology, 2022)
Certain lactic acid bacteria (LAB) are associated with immune modulatory activities including down-regulation of pro-inflammatory gene transcription and expression. While host antigen-presenting cells (APCs) and intestinal epithelial cells (IEC) can interact directly with both pathogenic and commensal bacteria through innate immune pattern recognition receptors, recent evidence indicates indirect communication through secreted molecules is an important inter-domain communication mechanism. This communication route may be especially important in the context of IEC and APC interactions which shape host immune responses within the gut environment. We have previously shown that the Lacticaseibacillus rhamnosus R0011 secretome (LrS) dampens pro-inflammatory gene transcription and mediator production from Tumor Necrosis Factor-α and Salmonella enterica serovar Typhimurium secretome (STS)-challenged HT-29 IECs through the induction of negative regulators of innate immunity. However, many questions remain about interactions mediated through these bacterial-derived soluble components and the resulting host immune outcomes in the context of IEC and APC interactions. In the present study, we examined the ability of the LrS to down-regulate pro-inflammatory gene transcription and cytokine production from STS-challenged T84 human IEC and THP-1 human monocyte co-cultures. Cytokine and chemokine profiling revealed that apically delivered LrS induces apical secretion of macrophage inhibitory factor (MIF) and down-regulates STS-induced pro-inflammatory mediator secretion into the apical and basolateral chambers of the T84/THP-1 co-culture. Transcriptional profiling confirmed these results, as the LrS attenuated STS challenge-induced CXCL8 and NFκB1 expression in T84 IECs and THP-1 APCs. Interestingly, the LrS also reversed STS-induced damage to monolayer transepithelial resistance (TER) and permeability, results which were confirmed by ZO-1 gene expression and immunofluorescence visualization of ZO-1 expression in T84 IEC monolayers. The addition of a MIF-neutralizing antibody abrogated the ability of the LrS to reverse STS-induced damage to T84 IEC monolayer integrity, suggesting a novel role for MIF in maintaining IEC barrier function and integrity in response to soluble components derived from LAB. The results presented here provide mechanistic evidence for indirect communication mechanisms used by LAB to modulate immune responses to pathogen challenge, using in vitro approaches which allow for IEC and APC cell communication in a context which more closely mimics that which occurs in vivo.